Influenza-Associated Disease Burden in Kenya: A Systematic Review of Literature. - Gideon O Emukule; John Paget; Koos van der Velden; Joshua A Mott (PLoS ONE)
Background In Kenya data on the burden of influenza disease are needed to inform influenza control policies. Methods We conducted a systematic review of published data describing the influenza disease burden in Kenya using surveillance data collected until December 2013. We included studies with laboratory confirmation of influenza, well-defined catchment populations, case definitions used to sample patients for testing and a description of the laboratory methods used for influenza testing. Studies with or without any adjustments on the incidence rates were included. Results Ten studies reporting the incidence of medically-attended and non-medically attended influenza were reviewed. For all age groups, the influenza positive proportion ranged from 5-10% among hospitalized patients, and 5-27% among all medically-attended patients (a combination of in- and outpatients). The adjusted incidence rate of hospitalizations with influenza among children < 5 years ranged from 2.7-4.7 per 1,000 [5.7 per 1,000 in children < 6 months old], and were 7-10 times higher compared to persons aged ≥ 5 years. The adjusted incidence of all medically-attended influenza among children aged < 5 years ranged from 13.0-58.0 per 1,000 compared to 4.3-26.0 per 1,000 among persons aged ≥ 5 years. Conclusions Our review shows an expanding set of literature on disease burden associated with influenza in Kenya, with a substantial burden in children under five years of age. Hospitalizations with influenza in these children were 2-3 times higher than reported in the United States. These findings highlight the possible value of an influenza vaccination program in Kenya, with children < 5 years and pregnant women being potentially important targets.